Hypertension and Its Contributing Factor among Adult People of Nepalgunj, Banke, Nepal - Tharu, Ramesh Prasad (Academia Research Journal, 2024)
Hypertension is a substantial public health concern on account of its extremely high prevalence all around the globe. It is referred to as a "silent killer" due to the fact that early-stage symptoms are rarely apparent until a medical emergency arises, such as chronic kidney disease, heart attack, or stroke. Therefore, this research aims to assess the contributing factor to hypertension among adult people of Belaspur -12, Nepalgunj, Banke. A descriptive cross-sectional research design was employed for the study, and primary data were collected through the implementation of a structured questionnaire and a non-probability convenience sampling technique. The analysis was carried out on the gathered data using descriptive and inferential statistics through SPSS (version 21.0). The findings of the research revealed that among total 120 respondents, nearly half of the respondents 56 (46.7%) had hypertension in 1- stage, while more than half of the respondents 64 (53.3%) had hypertension in its 2-stage. Based on the research findings, it can be inferred that the major factors contributing to hypertension among adult population were being alcohol consumption, consumption of animal source fat, overweight or obese, family history of hypertension.